Who was Sacagawea? - Fradin, Dennis B.; Taylor, Val Paul; Fradin, Judith Bloom (New York Grosset & Dunlap, 2002)
Learn how Sacagawea was only sixteen when she made her journey, why we honor her today, and why the expedition could have failed without her.
650
Keywords: Sacagawea; Sacagawea; Sacagawea -- Juvenile literature; Women -- Biography; Native Americans -- Biography; Shoshoni Indians -- Biography; Women -- Biography; Indians of North America -- Biography; Shoshoni Indians -- Biography; Shoshoni women -- Biography -- Juvenile literature